Carrier screening for Krabbe disease in an isolated inbred community. Issue 9 (1st July 2022) - Ezer, Shlomit; Zuckerman, Shachar; Segel, Reeval; Zlotogora, Joël
Abstract: Infantile Krabbe disease (OMIM 245200) is a severe, fatal autosomal recessive neurodegenerative disorder that is relatively frequent in two Muslims villages within Jerusalem. After the characterization of the founder mutation, a population carrier screening for Krabbe disease became a component of the Israeli program for the detection and the prevention of birth defects. Between 2010 and 2018, 3366 individuals were tested and among them 247 carriers for Krabbe disease were identified (7.3%). Most of the 21 carrier couples identified that had pregnancies after being informed that they were at risk used preventive measures including termination of pregnancies of affected fetuses. During the study period, eight children affected with Krabbe disease were born in the villages, four to couples not detected though the program. Twenty years after the beginning of the carrier screening program, Krabbe disease remained relatively frequent in the villages. The establishment of a genetic clinic in the villages may allow to improve the carrier screening program while giving individual counseling for the risk to the other genetic diseases existing in the villages.